The Quadruple Helix Model in Strengthening the Governance of Ambon City Government - Muhtar Muhtar; Jusuf Madubun; Atikah Khairunnisa; Fatimah Suatrat (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This study examines the role of the Quadruple Helix model in strengthening the governance of Ambon City Government amid the challenges of digital transformation, institutional coordination, and unequal public access to smart city services. The research aims to analyse the interaction patterns among government, academia, business, and civil society in supporting smart governance in Ambon City, as well as to identify the main constraints and strategic efforts required to optimize collaboration. This study uses a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews, focus group discussions, observation, and document analysis, and were analysed using thematic analysis. The results show that governance strengthening in Ambon City is increasingly supported by collaboration among Quadruple Helix actors through policy formulation, digital public service integration, public communication, and community participation. However, the collaboration still faces several challenges, including uneven digital infrastructure, limited digital literacy, incomplete regulatory consolidation, and partial system integration. The study concludes that the Quadruple Helix model contributes significantly to strengthening local governance, but its effectiveness depends on stronger institutionalization, wider digital inclusion, and more integrated governance systems. It is recommended that Ambon City Government strengthen smart city regulations, expand digital infrastructure, improve digital literacy, and deepen inter-agency system interoperability.